Thiol Based Redox Signaling in Plant Nucleus - Laura Martins; Laura Martins; José Abraham Trujillo-Hernandez; José Abraham Trujillo-Hernandez; Jean-Philippe Reichheld; Jean-Philippe Reichheld (Frontiers in Plant Science, 2018)
Reactive oxygen species (ROS) are well-described by-products of cellular metabolic activities, acting as signaling molecules and regulating the redox state of proteins. Solvent exposed thiol residues like cysteines are particularly sensitive to oxidation and their redox state affects structural and biochemical capacities of many proteins. While thiol redox regulation has been largely studied in several cell compartments like in the plant chloroplast, little is known about redox sensitive proteins in the nucleus. Recent works have revealed that proteins with oxidizable thiols are important for the regulation of many nuclear functions, including gene expression, transcription, epigenetics, and chromatin remodeling. Moreover, thiol reducing molecules like glutathione and specific isoforms of thiols reductases, thioredoxins and glutaredoxins were found in different nuclear subcompartments, further supporting that thiol-dependent systems are active in the nucleus. This mini-review aims to discuss recent progress in plant thiol redox field, taking examples of redox regulated nuclear proteins and focusing on major thiol redox systems acting in the nucleus.